2013
DOI: 10.1039/c3ta12860a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation via a solution method of La0.2Sr0.25Ca0.45TiO3 and its characterization for anode supported solid oxide fuel cells

Abstract: is a carefully selected composition to provide optimal ceramic and electrical characteristics for use as an anode support in solid oxide fuel cells. In this study we focus on the process optimization and characterization of A-site deficient perovskite, La 0.2 Sr 0.25 Ca 0.45 TiO 3 (LSCT A-), powders prepared via a solution method to be integrated into the SOFC anode supports. A Pechini method has been applied to successfully produce single phase perovskite at 900 C. Processing conditions have been modified to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…All materials were prepared by modified Pechini method described in detail previously [11]. Room temperature powder X-ray diffraction (XRD) was performed …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All materials were prepared by modified Pechini method described in detail previously [11]. Room temperature powder X-ray diffraction (XRD) was performed …”
Section: Methodsmentioning
confidence: 99%
“…The equilibrium value could not be reached even after 50 hours of reduction but the increase in conductivity value was gradual as time progressed. These two stages might be related to the fast removal of oxygen from the surface of the perovskite that is followed by a slow diffusion into the bulk of the micron size grains [11,18,19].…”
Section: Electrical Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…. 53 The porosity and lack of pre-reduction results in a drop of conductivity of approximately an order of magnitude, but constant conductivity values are obtained on redox cycling between pO 2 ¼ 10 À17 to 0.21 atm, with no sign of sample degradation or mechanical failure. The authors further noticed a marked increase in the redox kinetics, when impregnating the bars with ceria.…”
mentioning
confidence: 99%
“…Ti 4+ /Ti 3+ redox couple in the reducing atmosphere can accept electrons from hydrocarbon or H2 and promote dissociation. Oxygen-2p orbital and the empty conduction band from titanium-3d orbitals constitute the electronic energy band of 16,19,20 . It is shown that presence of Ni and CeO2 in LSCTA-backbone decreases the polarization losses and provides the stable performance of the cell during redox cycling 21 .…”
Section: Introductionmentioning
confidence: 99%